Ethical and legal landmines: Causal inference in special education decisions. Issue 9 (17th July 2017) - Sadeh, Shanna; Sullivan, Amanda L.
Abstract: In this article, we discuss conflict between law and science relative to the presumption in special education law that multidisciplinary teams and others identify the causes of problems giving rise to special education needs. First, we explain eligibility criteria, highlighting ambiguities therein and why criteria constitute a mandate for causal inference, and present illustrative examples of how judges have interpreted this mandate. Second, we discuss as a counterpoint school psychologists' ethical duties to conduct evaluations based on the best available science, and highlight the clear conflicts between the law, ethics, and research. We present the biopsychosocial model of development as a potential framework for reconciling one's legal duty to infer causation with the current evidence base. We conclude with implications for policy and practice and suggestions for future research.